Development of a Nationally Agreed Core Clinical Dataset for Childhood Onset Uveitis - Solebo, Ameenat Lola; Kellett, Salomey; Rahi, Jugnoo; Pattani, Reshma; Edelsten, Clive; Dick, Andrew D.; Denniston, Alastair; , The Pediatric Ocular Inflammation UNICORN Study Group; Solebo, Ms Ameenat Lola; Kellett, Ms Salomey; Dick, Professor Andrew D; Rahi, Professor Jugnoo; et al. (Frontiers in Pediatrics, 2022)
Background Childhood onset uveitis comprises a group of rare inflammatory disorders characterized by clinical heterogeneity, chronicity, and uncertainties around long term outcomes. Standardized, detailed datasets with harmonized clinical definitions and terminology are needed to enable the clinical research necessary to stratify disease phenotype and interrogate the putative determinants of health outcomes. We aimed to develop a core routine clinical collection dataset for clinicians managing children with uveitis, suitable for multicenter and national clinical and experimental research initiatives. Methods Development of the dataset was undertaken in three phases: phase 1, a rapid review of published datasets used in clinical research studies; phase 2, a scoping review of disease or drug registries, national cohort studies and core outcome sets; and phase 3, a survey of members of a multicenter clinical network of specialists. Phases 1 and 2 provided candidates for a long-list of variables for the dataset. In Phase 3, members of the UK’s national network of stakeholder clinicians who manage childhood uveitis were invited to select from this long-list their essential items for the core clinical dataset, to identify any omissions, and to support or revise the clinical definitions. Variables which met a threshold of at least 95% agreement were selected for inclusion in the core clinical dataset. Results The reviews identified 42 relevant studies, and 9 disease or drug registries. In total, 138 discrete items were identified as candidates for the long-list. Of the 41 specialists invited to take part in the survey, 31 responded (response rate 78%). The survey resulted in inclusion of 89 data items within the final core dataset: 81 items to be collected at the first visit, and 64 items at follow up visits. Discussion We report development of a novel consensus core clinical dataset for the routine collection of clinical data for children diagnosed with non-infectious uveitis. The development of the dataset will provide a standardized approach to data capture able to support observational clinical studies embedded within routine clinical care and electronic patient record capture. It will be validated through a national prospective cohort study, the Uveitis in childhood prospective national cohort study (UNICORNS).